Timing of pre-retrieval warnings matters in reducing memory errors in a repeated testing misinformation study - Alia N. Wulff; Jessica Karanian; Elizabeth Race; Ayanna K. Thomas (Scientific Reports)
Abstract Individuals are often exposed to information regarding previously witnessed events. The misinformation effect occurs when inaccurate post-event information impairs accuracy on a subsequent test of memory for the original event. The misinformation effect is increased when a test is given prior to exposure to post-event information, a phenomenon termed Retrieval Enhanced Suggestibility (RES). In two experiments, we investigated the value of general warnings prior to retrieval towards reducing RES, in situations where reconsolidation due to test related activation was likely. In both experiments, participants were exposed to an original event, and after a 24-hour retention interval either took a test about that original event or were not tested before being exposed to a narrative that included misleading details about the original event. In Experiment 1, a warning about the quality of the post-event narrative was then given followed by the final test. In Experiment 2, the warning and final test were delayed by 24 h. We found that warnings were effective in Experiment 1 in reducing RES, suggesting that even when initial testing supported learning of PEI, original details remained accessible. However, in Experiment 2, when warnings were delayed, participants were no longer able to effectively use them to reduce RES. These results suggest that warnings are most effective when given in close temporal proximity to misinformation.